Caracterização molecular dos mecanismos de resistência às polimixinas em isolados ambientais de Klebsiella variicola - Pinto, Michael Henrique Lenzi [UNIFESP] (2020)
Polymyxins are cationic compounds used as last-resort treatment of multiresistant gram-negative bacteria. The bactericidal action of polymyxins occurs when there is an electrostatic interaction between the positive charge of polymyxins and the negative charge of lipid A. The return to use of polymyxins in clinical treatment and continued use in veterinary medicine has caused an increase in reports of bacteria resistant to these compounds, especially in the hospital settings. Lipid A modification is the main mechanism of resistance polymyxin resistance phenotype. These modifications can be mediated chromosome via two-component systems (TCS), or via mobile elements MCR protein. This study aims to investigate isolates of polymyxins resistant Klebsiella variicola from migratory birds and to characterize the mechanisms responsible for this phenotype. A total of 339 gram-negative microorganisms were selected from of environmental samples from migratory birds collected at the Zoo of São Paulo in 2012. The polymyxin resistant gram-negative isolates from natural sources were identified by MALDI-TOF MS. Bacterials belonging to the same species K. variicola were analized to genetic similarity analysis by PFGE. After, the susceptibility profile to the other antimicrobials was determined by the dilution agar technique and interpreted following EUCAST/BrCAST guidelines. K. variicola isolates were to submit to detection of polymyxin resistance factors by phenotypic and molecular technique, followed by membrane load analysis. To the characterization the genes responsible for polymyxin resistance, the Whole Genome Sequencing (WGS) was performed by Illumina MiSeq methodology. Three polymyxins resistants K. variicola isolates (M14, M15 and M50) were identified. Among these, it was possible to visualize two different clonal groups, where M15 is a subclone of M14 and M50 a different clone. MLST analysis showed that M14 and M15 belong to ST137 and M50 to ST167. Susceptibility tests have shown that the three isolates are susceptible to all antimicrobials tested except polymyxins. There was no detection of mcr gene variants in these isolates. WSG analysis demonstrated mutations that cause protein change in genes responsible for polymyxin resistance in K. pneumoniae (mgrB, phoQ and pmrB). These same genes showed high transcriptional levels observed in the qRT-PCR demonstrating correlation with polymyxin resistance in the three isolates.